Rosemary distillation residues reduce lipid oxidation, increase alpha-tocopherol content and improve fatty acid profile of lamb meat. (February 2018) - Yagoubi, Y.; Joy, M.; Ripoll, G.; Mahouachi, M.; Bertolín, J.R.; Atti, N.
Abstract: The experiment studied the effects of rosemary distillation residues (RR) intake on lamb meat quality, oxidative stability and fatty acid (FA) profile. Barbarine lambs of Control group were fed 600 g of hay, which was substituted by 600 g of pellets containing 60 and 87% of RR for RR60 and RR87 groups; all animals received 600 g of concentrate. Meat protein and fat content was similar for 3 treatments. Lipid oxidation was strongly reduced with RR diets. Both RR diets resulted in a higher α- tocopherol content in muscle. The metmyoglobin and deoxymyoglobin percentages were similar for all groups; however oxymyoglobin was higher for RR groups. The saturated (SFA) and unsaturated FAs (UFA) were unaffected by the diets. However, the PUFA, n-6 and n-3 were higher for RR groups. In conclusion, rosemary residues resulted in higher vitamin E content, so it enhanced the oxidative status and improved the fatty acid profile of lamb meat. Highlights: Meat n − 6/n − 3 ratio of lambs fed rosemary distillation residues was lower than hay one. The meat produced with rosemary distillation residues has a high vitamine E content. The rosemary distillation residues permit higher oxymyoglobin. The oxidative stability was higher for lambs fed rosemary distillation residues.